2019
DOI: 10.4097/kja.d.18.00173
|View full text |Cite
|
Sign up to set email alerts
|

Sequential intrathecal injection of fentanyl and hyperbaric bupivacaine at different rates: does it make a difference? A randomized controlled trial

Abstract: Background Previous studies have shown that sequential intrathecal injection of fentanyl and hyperbaric bupivacaine for cesarean section (CS) anesthesia provides a superior anesthetic effect than use of bupivacaine alone, and prolongs postoperative analgesia. Herein, we investigated whether rapid intrathecal injection of fentanyl followed by slow injection of hyperbaric bupivacaine affects the duration of postoperative analgesia, the effectiveness of anesthesia, and hemodynamic status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
8
2
Order By: Relevance
“…et al study who found no difference in regression time to bromage 0 between premixed and sequential groups. [4] [13] We observed that in our study, clinically maximum analgesia lasted in premixed group after the surgery followed by sequential groups but statistically it was nonsignificant. However Hussien RM et al concluded that sequential injection of IT fentanyl when given rapidly, it prolongs postoperative analgesia.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…et al study who found no difference in regression time to bromage 0 between premixed and sequential groups. [4] [13] We observed that in our study, clinically maximum analgesia lasted in premixed group after the surgery followed by sequential groups but statistically it was nonsignificant. However Hussien RM et al concluded that sequential injection of IT fentanyl when given rapidly, it prolongs postoperative analgesia.…”
Section: Discussioncontrasting
confidence: 47%
“…When fentanyl was injected in a rapid sequential manner, resulted in increased somatic analgesia with no effect on degree or level of motor block, induced by LA. [13] In our study regression time to sensory block T10 was found statistically significant between the groups (p=.002), but on comparison between premixed and sequential group no statistically significant difference was seen. Hussien RM et.al.and Desai S et al also reported similar result.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations